A new two-hit animal model for schizophrenia research: Consequences on social behavior - Kristina Hakenova; Anna Mikulecka; Kristina Holubova; Marketa Chvojkova; Romana Slamberova; Jana Jurcovicova; Barbora Cechova; Silvester Ponist; Jiri Horacek; Karel Vales (IBRO Neuroscience Reports)
Schizophrenia, a profoundly impactful neuropsychiatric disorder, has been the subject of extensive research using animal models. However, certain important aspects remain understudied, including assumed long-term consequences of psychotic episodes on negative symptoms development and progression. Addressing these limitations, we proposed a novel animal model in male rats based on early postnatal immune activation triggered by lipopolysaccharide (LPS), serving as the predisposing factor (1st hit). As the 2nd hit, representing psychotic-like episodes, we implemented a multi-episodic co-treatment with dizocilpine (MK-801) and amphetamine (AMP), spanning multiple developmental periods. The animals were tested in two social behavioral assays in adolescence and adulthood to investigate whether a social deficit would arise. In addition, we evaluated the level of oxytocin (OT), a neuropeptide relevant to social behavior, in selected brain regions. In the social interaction test, when animals could freely interact in the open field and express their social behavioral profile entirely, social behavior decreased in adolescent experimental animals. In the social approach test in the Y maze, all animals, irrespective of treatment, preferred conspecific over an indifferent object and novel rat over a familiar rat. Further, the results revealed that the OT content in the hypothalamus increased with age. In the proposed model, social interaction in the open field was decreased in adolescent but not in adult rats, indicating that the pharmacological manipulations caused only transient age-dependent changes. The study was thus in certain aspects successful in creating a novel approach to model social deficit potentially relevant to schizophrenia; other findings require further investigation.